Vertical handover decision schemes in fourth generation heterogeneous cellular networks: A comprehensive study - Hushairi, Zen; Adnan, Mahmood; Shadi, M. S. Hilles (IGI Global, 2018)
Vertical Handover Decision (VHD) algorithms are indispensable components of forthcoming 4G heterogeneous wireless networks architecture – so as to provide requisite Quality of Service to an assortment of applications anywhere at any time, while allowing seamless roaming in highly dynamic scenarios (i.e. multitude of access network technologies that vary in bandwidth, latency, monetary cost, etc.) using Mobile Terminals (MTs) enabled with multiple access interfaces. In this article, a critical review of the existing VHD algorithms has been carried out as an effort to update the previous studies. To offer a methodical contrast, recently published VHD algorithms have been classified into four major classes depending on the key handover decision criterion used, i.e. RSS based algorithms, bandwidth based algorithms, cost function based algorithms, and the combination algorithms. Moreover, operational fundamentals, advantages, and disadvantages of exemplary VHD algorithms for each class have been presented to assess the tradeoffs between their intricacy of implementation and the efficacy. Copyright © 2018, IGI Global. Copying or distributing in print or electronic forms without written permission of IGI Global is prohibited.